Alterações microbiológicas, de fertilidade e de produtividade do arroz de terras altas em diferentes manejos de solo e água - dos Santos, Talles Eduardo Borges [UNESP]; Nakayama, Fernando Takayuki [UNESP]; Arf, Orivaldo [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP] (My University, 2008)
In Brazil, the upland rice culture system is predominant, but its water supply depends of precipitation and its distribution. Some practices or disturbances on soil conditions may cause alterations that can be detected by microorganisms, which are quite sensitive. This experiment was developed to study microbiological alterations (microbial biomass carbon (MBC), released CO2 (C-CO2), metabolic quotient (qCO2) and mycorrhization), as well as alterations in soil fertility and productivity of upland rice, cultivated under different soil and water managements. Cultivar BRS Talento was used in the experiment. The experimental design was a completely randomized block design, with four replications, using three soil managements: no-tillage (NT), heavy disk + leveling disk harrowing (HL), and chisel plowing + leveling disk harrowing (CL), plus three water managements: no irrigation (WD0); water depth 1 (WD1), with irrigation at the reproductive and maturation periods; and water depth 2 (WD2), with irrigation throughout the rice cycle. Autochthones arbuscular mycorrhizal fungi proved to be sensitive to soil and water management. The NT presented the highest values for MO, Ca, SB and V% and the lowest for H+Al. This management, together with irrigation at the reproductive and maturation periods of BRS Talento cultivar, promoted goods results for crop yield and microbiology characteristics.
Microbiological, fertility and productivity alterations in upland rice under different soil and water managements
Keywords: Arbuscular mycorrhizal fungi; Irrigation; Microbial activity; Minimum tillage; No-tillage